PENGARUH INOVASI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING UMKM KULINER - Lestari, Inda; Astuti, Miguna; Ridwan, Hariyanto (Economic Faculty, Attahiriyah Islamic University, 2019)
This research was conducted to analyze the effect of innovation orientation and entrepreneurship on the competitive advantage of culinary MSMEs in the Cilandak Barat area, South Jakarta. The population used for this study was 36 actors in the culinary field of SMEC. The sampling technique uses a saturated sampling method. The data analysis tool used is PLS 3.0. The results of this study indicate that the innovation variable has a significant influence on the culinary competitiveness of SMEC. And, entrepreneurial orientation has a significant influence on the culinary competitiveness of SMEC. The researcher suggests SMECs to pay attention to other factors that can influence competitive advantage. Keywords: Innovation, Entrepreneurship Orientation, Competitive Advantage